An Estimated Model of Employer and Non-Employer Entrepreneurship - Md Mobarak Hossain; Frank M. Fossen; Sankar Mukhopadhyay (Institute of Labor Economics (IZA), 2025)
What motivates individuals to become entrepreneurs and create jobs? We develop and estimate a dynamic structural microeconometric model that accounts for both employer and non-employer entrepreneurs. Individuals in each period choose to work as an employee, as one of the two entrepreneur types, or remain non-employed. Different work experiences may affect earnings in the three sectors differently. The estimated model replicates key data patterns. The results suggest that experience in employment provides positive returns in entrepreneurship, but entrepreneurial experience does not have positive returns in employment. The model is used to simulate how policy scenarios would affect individuals' entrepreneurial choices.
Keywords: J22; J23; L26; C61; 330; dynamic structural model; employer; entrepreneurship; life cycle